Ten-year clinical outcomes of everolimus- and biolimus-eluting coronary stents vs. everolimus-eluting bioresorbable vascular scaffolds—insights from the EVERBIO-2 trial - Bengueddache, Samir; Cook, Malica; Lehmann, Sonja; Arroyo, Diego; Togni, Mario; Puricel, Serban; Cook, Stephane (Frontiers in Cardiovascular Medicine, 2024)
Background. Bioresorbable vascular scaffold (BVS) have been developed to potenHal soluHon to miHgate late complicaHons associated with drug-eluHng metallic stents (DES) in percutaneous coronary intervenHon (PCI) for coronary artery disease (CAD). While numerous studies have compared BVS to DES, none have assessed clinical outcomes beyond 5 years.Objec/ves. This study aimed to compare the 10-year clinical outcomes of paHents treated with BVS versus DES.Stents with Everolimus-EluHng Bioresorbable Vascular Scaffold) is a single-center, assessorblinded, randomized controlled trial, enrolled 240 paHents allocated in a 1:1:1 raHo to receive BVS, everolimus-eluHng stents (EES), or biolimus-eluHng stents (BES). Clinical follow-up was scheduled to 10 years.Results. Clinical follow-up was completed in 222 paHents (93%) at the 10-year mark. The rate of device-oriented composite events (DOCE) was 28% in the DES group and 29% in the BVS group (p=0.72) at 10 years. Similarly, the rate of paHent-oriented composite events (POCE) was 55% in the DES group and 49% in the BVS group (p=0.43) at 10 years. Notably, the rate of myocardial infarcHon (MI) within the target vessel was 5% in the BVS group and 0% in the BES group (p=0.04), while the rate of any MI was 10% in the BVS group and 2% in the BES group (p=0.04). AddiHonally, the rate of ARC possible stent thrombosis was 3% in the BVS group and 0% in the DES group (p=0.04).Ten years clinical DOCE and POCE were similar between BVS and DES but individual outcomes of stent thrombosis were higher (3%) in BVS compared to DES.